Management of Haemabartonellosis in a Pitbull dog - Sofyan, Miyayu Soneta; Pertiwi, Herinda; Rusman, Aifa Hazurin; Rosman, Nabiha; Kamaludeen, Juriah; Dadi, Tri Bhawono; Ira Sari Yudaniayanti (Indian Veterinary Association, 2020)
A three years old, male dog, weighing 19 kg, of Pitbull breed presented for general check up and blood test at Veterinary Teaching Hospital of Airlangga University, Surabaya. Based on chemistry blood test, complete blood count (CBC) and blood parasite test the dog was diagnosed with Haemabartonellosis due Mycoplasmahaemocanis with anaemia. It was treated with haematinics and broad-spectrum antibiotics, doxycycline. The dog was totally back to the normal condition after prolonged treatment.